A state-of-the-art review of hydropower in Malaysia as renewable energy: Current status and future prospects. (November 2018) - Hossain, Monowar; Huda, A.S.N.; Mekhilef, Saad; Seyedmahmoudian, Mehdi; Horan, Ben; Stojcevski, Alex; Ahmed, Mahrous
Abstract: The gradual depletion of fossil-fuel-based energy resources and the growing rate of greenhouse gas emission are two of the most significant global concerns in recent years. These concerns have resulted in an increasing demand for the utilization of renewable energy resources. From among all renewable resources, hydropower is the leading contributor to grid-connected electricity in the world. In this article, the hydropower potential in Malaysia, current and future prospects of large and small-scale hydropower development, and issues and challenges related to hydropower development are described. Small hydropower promotion techniques, government initiatives, and the advantages and barriers to small hydropower development are also included. Highlights: Hydropower potential in Malaysia. Current and future prospects of large and small scale hydropower development. Issues and challenges related to hydropower development. Small hydropower promotion techniques, government initiatives and advantages and barriers towards small hydropower development.